2007
DOI: 10.1523/jneurosci.2156-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging of Primary Visual Cortex Using Flavoprotein Autofluorescence

Abstract: Neuronal autofluorescence, which results from the oxidation of flavoproteins in the electron transport chain, has recently been used to map cortical responses to sensory stimuli. This approach could represent a substantial improvement over other optical imaging methods because it is a direct (i.e., nonhemodynamic) measure of neuronal metabolism. However, its application to functional imaging has been limited because strong responses have been reported only in rodents. In this study, we demonstrate that autoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 50 publications
9
56
0
Order By: Relevance
“…The close temporal correlation of the spinal AFI response to electrical input is in agreement with other in vivo AFI studies using direct electrical stimulation of the somatosensory cortex (Shibuki et al, 2003) or cerebellum (Reinert et al, 2004;Gao et al, 2006;Wang et al, 2009). The somatotopic distribution of the AFI response that we found after sciatic nerve stimulation is in agreement with in vivo AFI studies using tactile, auditory, and visual stimuli and AFI recordings from the somatosensory cortex (Shibuki et al, 2003;Murakami et al, 2004), barrel cortex (Weber et al, 2004), auditory cortex (Takahashi et al, 2006;Kubota et al, 2008), or visual cortex (Tohmi et al, 2006;Husson et al, 2007), respectively. Furthermore, the absence of an AFI response after electrical blockade of the sciatic nerve by lidocaine indicated that the AFI signal was indeed generated by sciatic nerve input.…”
Section: Discussionsupporting
confidence: 91%
“…The close temporal correlation of the spinal AFI response to electrical input is in agreement with other in vivo AFI studies using direct electrical stimulation of the somatosensory cortex (Shibuki et al, 2003) or cerebellum (Reinert et al, 2004;Gao et al, 2006;Wang et al, 2009). The somatotopic distribution of the AFI response that we found after sciatic nerve stimulation is in agreement with in vivo AFI studies using tactile, auditory, and visual stimuli and AFI recordings from the somatosensory cortex (Shibuki et al, 2003;Murakami et al, 2004), barrel cortex (Weber et al, 2004), auditory cortex (Takahashi et al, 2006;Kubota et al, 2008), or visual cortex (Tohmi et al, 2006;Husson et al, 2007), respectively. Furthermore, the absence of an AFI response after electrical blockade of the sciatic nerve by lidocaine indicated that the AFI signal was indeed generated by sciatic nerve input.…”
Section: Discussionsupporting
confidence: 91%
“…Note that the active area determined from AF is considerably smaller than that obtained from LSI. In addition, onset of the latter signal is delayed relative to the former, supporting the concept that the oxidative metabolism response is faster and more localized to neuronal activation than the blood flow response ͑with permission from: Weber et al, 2004͒. tofluorescence responses were recently shown to accurately reflect the functional architecture in cat primary visual cortex (Husson et al, 2007). The high quality of the orientation pinwheel maps obtained by this method was at least as good as that of the maps obtained by intrinsic imaging.…”
Section: More Direct Measurements Of Cerebral Oxidative Metabolismsupporting
confidence: 58%
“…Also, the hemodynamic reflectance signal is of a fundamentally different origin than flavoprotein autofluorescence and is imaged at different wavelengths using reflectance. Hemodynamics contributes little, if any, to the flavoprotein signal (Husson et al 2007;Reinert et al 2004;Shibuki et al 2003). Also, several properties of the low-frequency oscillations in the tg mouse are not consistent with a systemically generated vasomotor signal, particularly the loss of the response to PF stimulation when high power domains were evident.…”
Section: Discussionmentioning
confidence: 99%